This Kompilasi Hukum Islam (KHI) sebagai Wujud Adaptasi Hukum Islam dalam Sistem Hukum Nasional Indonesia - Muhammad Jaidi; Nazila Naura Azqiana (Institut Agama Islam Darul Ulum Kandangan, 2025)
This study discusses the historical process, legal politics, and significance of the Compilation of Islamic Law (CIL) as a form of adaptation of Islamic law into Indonesia's national legal system. Through a historical-normative approach, this study investigates the background of the formation of the CIL during the New Order era, as well as its impact on the existence of Islamic law in religious court practices. The CIL is not only a codification of Islamic family law in Indonesia, but also a symbol of the acceptance of Sharia values in the national legal system based on Pancasila and the 1945 Constitution. Thus, the CIL is important in building an Indonesian legal system based on social justice and the religious values of the nation. Keywords: Adaptation of Islamic Law, Indonesian National Law, Compilation of Islamic Law (CIL), Legal Policy, Religious Court System.